Does the use of a university lecturer as a visiting tutor support learning and assessment during physiotherapy students' clinical placements? A survey of higher education institution providers. Issue 4 (December 2016) - Dean, M.; Levis, A.
Abstract: Objectives: To establish the rationale for using a lecturer as a visiting tutor, and to identify the activities undertaken during clinical placements to support student learning and assessment in practice. Design: A secure electronic survey was used to incorporate qualitative and quantitative data collection procedures. Setting: Thirty-three higher education institution (HEI) providers of physiotherapy education in the UK, registered with the Chartered Society of Physiotherapy. Participants: UK HEI physiotherapy placement coordinators. Main outcome measures: A questionnaire was used to examine HEI perceptions. A pilot focus group consultation informed the questionnaire content. Surveys were analysed based on the proportion of responses to closed questions on an adapted Likert scale, with further thematic analysis of open questions. Results: All 25 respondents (25/33, 76%) indicated their provision of support for students and clinical educators throughout their clinical placements. 'Face-to-face' engagement during the placement visit was viewed as essential to guide the clinical educator to provide a consistent approach to learning and assessment strategies; ensuring cohesion between theoretical and clinical components of the curriculum was viewed as a core objective by visiting academic tutors. However, the emergent themes highlighted key differences between HEIs' perspectives of what this support for clinical placement learning should entail. Conclusions: The majority of HEIs endorse the use of a lecturer as a visiting tutor to inform and maintain the standard of learning and assessment within the clinical placement. However, the value of this interaction requires confirmation via other stakeholders, and exploration of other forms of non-face-to-face support processes warrant further investigation.